Boosting Reading Comprehension of Grade 6 Pupils through Comic-Based Reading Materials: An Investigation of Effectiveness - Anjo Tanala (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
This quasi-experimental study was conducted to determine the effectiveness of Comic-Based Reading Materials tin enhancing the reading comprehension of Grade 6 pupils in Sampiruhan Elementary School. The researcher crafted these Comic-Based reading materials, which are reading texts and/or literatures adapted from the DepEd R4A Pivot Modules in English transformed into comics-type reading materials. These served as the instrument of the study. The result of the study was analyzed using the outcome of the pupils’ pretest and posttest. Two group of pupils served as the participants of the study. Each group was composed of thirty (30) pupils each chosen using a match-pairing from the result of their pretest. The participants’ baseline on reading comprehension were measure using a standardized test from the Phil-Iri. The comic-based reading materials crafted by the researcher was implemented to the experimental group while the comparison group utilized the common materials from the DepEd R4A Pivot Modules provided by the Department of Education. Independent and Paired Sample T-test were used to analyze the data and answer the inferential questions from the study. After the implementation of the instrument, the researcher found out that the experimental group performed better on their posttest from their pretest. In addition, the experimental group also outscored the comparison group during their posttest. Between the scores of the two groups a significant difference was obviously observed. This revealed the effectiveness of the comic-based reading materials to the reading comprehension of grade 6 pupils. Hence, the hypothesis stating that there is no significant difference between the posttest of the two groups was rejected.